Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

If [tex]\( x+2 \)[/tex] is a factor of [tex]\( x^3 - 6x^2 - 11x + k \)[/tex], then [tex]\( k = \)[/tex] [tex]\(\square\)[/tex]

Sagot :

To determine the value of [tex]\( k \)[/tex] such that [tex]\( x+2 \)[/tex] is a factor of the polynomial [tex]\( x^3 - 6x^2 - 11x + k \)[/tex], we will use the Factor Theorem. The Factor Theorem states that [tex]\( x+c \)[/tex] is a factor of a polynomial [tex]\( P(x) \)[/tex] if and only if [tex]\( P(-c) = 0 \)[/tex].

1. According to the Factor Theorem, if [tex]\( x+2 \)[/tex] is a factor of [tex]\( x^3 - 6x^2 - 11x + k \)[/tex], then we must have:
[tex]\[ f(-2) = 0 \][/tex]
Where [tex]\( f(x) = x^3 - 6x^2 - 11x + k \)[/tex].

2. Substitute [tex]\( x = -2 \)[/tex] into the polynomial [tex]\( f(x) \)[/tex]:
[tex]\[ f(-2) = (-2)^3 - 6(-2)^2 - 11(-2) + k \][/tex]

3. Calculate each term individually:
[tex]\[ (-2)^3 = -8 \][/tex]
[tex]\[ - 6(-2)^2 = -6(4) = -24 \][/tex]
[tex]\[ - 11(-2) = 22 \][/tex]

4. Now, combine these values:
[tex]\[ f(-2) = -8 - 24 + 22 + k = 0 \][/tex]

5. Simplify the equation:
[tex]\[ -8 - 24 + 22 + k = 0 \][/tex]
[tex]\[ -8 - 24 = -32 \][/tex]
[tex]\[ -32 + 22 = -10 \][/tex]
Therefore, we have:
[tex]\[ -10 + k = 0 \][/tex]
6. Solving for [tex]\( k \)[/tex] gives:
[tex]\[ k = 10 \][/tex]

Hence, the value of [tex]\( k \)[/tex] is [tex]\( \boxed{10} \)[/tex].
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.